2009
DOI: 10.1016/j.phytochem.2009.07.038
|View full text |Cite
|
Sign up to set email alerts
|

An experimental approach to study the biosynthesis of brominated metabolites by the red algal genus Laurencia

Abstract: The production of labeled brominated metabolites with radioactive 82 Br in Laurencia species was investigated as part of a study of the biosynthesis of halogenated metabolites from species belonging to the red algal genus Laurencia (Rhodomelaceae, Ceramiales Br-containing metabolites. In the case of the laurencin-producing race of L. nipponica, laurencin and deacetyllaurencin were found to be produced in approximately 1:1 ratio, though laurencin is the major metabolite in the wild sample. Furthermore, when cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Furthermore, when Laurencia spp. specimens were cultured in the dark, the production rates of brominated metabolites were diminished [58].…”
Section: "Corps En Cerise"mentioning
confidence: 99%
“…Furthermore, when Laurencia spp. specimens were cultured in the dark, the production rates of brominated metabolites were diminished [58].…”
Section: "Corps En Cerise"mentioning
confidence: 99%
“…495,496 In 1992, the same group described a single-step, LPO-catalyzed intramolecular cyclization of (3Z,6S,7S)-laurediol to produce laureatin (481) and its key intermediate prelaureatin (485). 497 The result also suggests that laurediols are the precursors of Laurencia derived ACGs, and that LPO has very low substrate specificity.…”
Section: Biosynthesis Of C 15 -Acetogeninsmentioning
confidence: 99%
“…The work demonstrated that the use of 82 Br provides an effective approach to investigating the biosynthesis of brominated metabolites in Laurencia species, though the half-life of 82 Br is very short (35.3 h) as compared with those of the more commonly used tracers 14 C (5730 y) and 3 H (12.3 y). 485 …”
Section: Biosynthesis Of C 15 -Acetogeninsmentioning
confidence: 99%
“…In particular, species of Laurencia are known to be the richest producers of halogenated secondary metabolites with diverse and unique structural features depending on species, localities and season [5]. Laurencia species produce bromine-containing compounds in much larger numbers than either chlorine-or iodine-containing ones whereas, the Clcontaining compounds usually also possess Br atom(s) [6]. A large number of these compounds have been obtained from Laurencia species having an intracellular, membrane-bound vesicles known as "corps en cerise" (cherry bodies) in the outer cell layer (the cortical layer) where, these inclusions are considered as a synthesis and/or storage sites of halogenated secondary metabolites [7].…”
Section: Introductionmentioning
confidence: 99%